Turn Down the Heat : Climate Extremes, Regional Impacts, and the Case for Resilience - Potsdam Institute for Climate Impact Research and Climate Analytics (Washington, DC: World Bank, 2013)
A Report for the World Bank by the Potsdam Institute for Climate Impact Research and Analytics.